IMPLEMENTATION OF SIMULATOR LEARNING MEDIA ON CONTAINER SHIPLOADING HANDLING PLANNING FOR VOCATIONAL EDUCATION CADETS - Tri Cahyadi; Agus Dina Mirianto; Novita Vindri Harini; Luri Krisnawati (Jurnal Maritim Malahayati, 2022)
The era of Education 4.0 is education characterized by the use of digital technology in the learning process. The teaching and learning process that is integrated with appropriate technology will support the success of education in this era. Vocational education is a tertiary institution that supports the mastery of applied skills in certain fields. Shipping is one of these vocational fields. Shipping is closely related to the port and the loading and unloading process in it. Generally, this loading and unloading process takes quite a long time and causes congestion. The reason is that it is difficult to find an instant way to arrange items that are easy to pick up in the order they arrive. The purpose of this study is to develop a web-based simulator to determine the right stowage plan for the arrangement of containers on a transport ship and implement it in learning in shipping vocational education (Polteknik Pelayaran Surabaya and Politeknik Pelayaran Malahayati). With the RnD type, this research produces a simulator design that can display ship mileage, ship data, container data, container arrangement on ships, as well as ship stability and displacement calculations. It is hoped that with this simulator, the loading and unloading process at the port will be faster and congestion can be reduced. When implemented in Cargo Handling and Stowage Include Cargo Space and Reporting classes and ship construction and stability, the simulator media had a positive effect on cadets (87% through the results of the response questionnaire and 86.5% on competency tests).